2016
DOI: 10.1097/rlu.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Preparation on the Diagnostic Performance of 18F-FDG PET in Cardiac Sarcoidosis

Abstract: F-FDG PET/CT plays an integral role in the diagnosis of cardiac sarcoidosis. Diagnostic accuracy is affected by fasting duration and means of cardiomyocyte glucose uptake suppression before scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…They conclude that duration of fasting and heparin administration significantly affected the diagnostic odds ratio (P = .01 and .04, respectively), whereas a high fat low cholesterol diet did not have a significant effect (P = .17). 6 Nonspecific findings that may indicate failed suppression, and/or physiologic uptake and make image interpretation challenging included diffuse myocardial activity exceeding liver uptake or uptake in the lateral wall and/or ring shaped/circumferential basal uptake (Nensa et al doi: 10.1007/s12350-016-0443-1) 7 or papillary muscle uptake. 8,9 Diffuse FDG uptake in the entire left ventricular wall without focal uptake generally does not indicate disease as cardiac sarcoidosis is histopathologically known to be localized and not diffuse.…”
Section: See Related Article Pp 86-99mentioning
confidence: 99%
“…They conclude that duration of fasting and heparin administration significantly affected the diagnostic odds ratio (P = .01 and .04, respectively), whereas a high fat low cholesterol diet did not have a significant effect (P = .17). 6 Nonspecific findings that may indicate failed suppression, and/or physiologic uptake and make image interpretation challenging included diffuse myocardial activity exceeding liver uptake or uptake in the lateral wall and/or ring shaped/circumferential basal uptake (Nensa et al doi: 10.1007/s12350-016-0443-1) 7 or papillary muscle uptake. 8,9 Diffuse FDG uptake in the entire left ventricular wall without focal uptake generally does not indicate disease as cardiac sarcoidosis is histopathologically known to be localized and not diffuse.…”
Section: See Related Article Pp 86-99mentioning
confidence: 99%
“…A fasting period of at least 12 hours, [1][2][3][4] as well as low-carbohydrate diet, [5][6][7][8][9][10][11][12] have been proven beneficial for decreasing the normal myocardial uptake of 18 Ffluorodeoxyglucose ( 18 F-FDG) and for enhancing the detectability of inflammatory and/or infectious heart diseases by 18 F-FDG positron emission tomography ( 18 F-FDG-PET). Unfortunately, none of these previously reported protocols enable the complete and consistent suppression of the cardiac uptake of 18 F-FDG.…”
Section: Introductionmentioning
confidence: 99%
“…25 A total of 16 studies and 559 patients were included in the final analysis, which showed that intravenous heparin and duration of fasting were positively associated with the diagnostic odds ratio (coefficient, 2.90; P = 0.04 and coefficient, 0.282; P = 0.01 respectively), as opposed to a high fat-low carb dietary preparation (coefficient, 1.71; P = 0.17). 25 Despite its thought-provoking findings, the meta-analysis did have some noteworthy limitations.…”
mentioning
confidence: 99%
“…25 A total of 16 studies and 559 patients were included in the final analysis, which showed that intravenous heparin and duration of fasting were positively associated with the diagnostic odds ratio (coefficient, 2.90; P = 0.04 and coefficient, 0.282; P = 0.01 respectively), as opposed to a high fat-low carb dietary preparation (coefficient, 1.71; P = 0.17). 25 Despite its thought-provoking findings, the meta-analysis did have some noteworthy limitations. First, it only included studies assessing patients with suspected or known sarcoidosis; second, the lack of a diagnostic reference standard for cardiac sarcoidosis makes the findings on sensitivity and specificity of FDG-PET somewhat challenging to interpret; and third, the majority of the studies included were small and the preparation methods employed were widely variable.…”
mentioning
confidence: 99%
See 1 more Smart Citation